STRUKTUR DAN KOMPOSISI AREAL HUTAN BEKAS TERBAKAR DI HUTAN PENELITIAN BRON, WAREMBUNGAN - Alfi Klaudio Gabi; Johny S. Tasirin; Maria Y. M. A. Sumakud (Universitas Sam Ratulangi, 2022)
ABSTRAK This study aims to determine the structure and composition of the vegetation in the Bron Research Station after the fire. This research was conducted at the Bron Research Station, Warembungan, North Sulawesi in November-December 2020. Observations were made in 1 plot measuring 1 ha. The results showed that the structure and composition of the post-fire Bron Research Forest had 22 plant species with 15 families. There are 10 species at the tree level, 3 species at the pole level, 5 species at the sapling level and 4 species at the cattle level. At the tree level, it was dominated by Ficus benjamina with an IVI 71.3%, at the pole level found 3 species dominated by Piper aduncum with an IVI 132.1%, 5 species at the sapling level dominated by Piper aduncum with an IVI 207.0%. The forest floor vegetation found 9 plant species dominated by Selaginella plana with an IVI 74.2%, in the forest floor vegetation community, including 3 species with tree habitats, namely Ficus benjamina IVI 6.7%, Caryota mitis IVI 6.7% and Piper aduncum IVI 21.9%. Biodiversity in the Bron Research Forest has Shannon-Wiener index 2.38; Margalef index 4.06 and Evenness index 0.77. Keywords: Structure and composition, burnt forest, Bron Research Forest, Warembunga